2017
DOI: 10.1111/joa.12715
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of the ankle extensor muscle‐tendon units and the biomechanical implications for bipedal hopping locomotion in the post‐pouch kangarooMacropus fuliginosus

Abstract: Bipedal hopping is used by macropods, including rat-kangaroos, wallabies and kangaroos (superfamily Macropodoidea). Interspecific scaling of the ankle extensor muscle-tendon units in the lower hindlimbs of these hopping bipeds shows that peak tendon stress increases disproportionately with body size. Consequently, large kangaroos store and recover more strain energy in their tendons, making hopping more efficient, but their tendons are at greater risk of rupture. This is the first intraspecific scaling analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 43 publications
(118 reference statements)
0
46
1
Order By: Relevance
“…The largest extant artiodactyls are an order of magnitude more massive than the largest extant macropods while the smallest of both clades included in this study are ~1-2 kg. It would be unwise to extrapolate macropod scaling trends beyond the current series, because bipedal hopping was likely not a feature of the extinct giant kangaroos and may not be physiologically possible beyond ~160 kg [7][8][9][10]. Janis et al (2014) suggested that large, extant kangaroos are functionally specialised for hopping in contrast to their larger extinct kin that did not hop, somewhat similar to the medium-sized, gracile and hyper-athletic cheetah (Acinonyx jubatus, M = 35-70 kg) compared to bigger and more robust felids such as lion (Panthera leo, M = 120-250 kg) [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The largest extant artiodactyls are an order of magnitude more massive than the largest extant macropods while the smallest of both clades included in this study are ~1-2 kg. It would be unwise to extrapolate macropod scaling trends beyond the current series, because bipedal hopping was likely not a feature of the extinct giant kangaroos and may not be physiologically possible beyond ~160 kg [7][8][9][10]. Janis et al (2014) suggested that large, extant kangaroos are functionally specialised for hopping in contrast to their larger extinct kin that did not hop, somewhat similar to the medium-sized, gracile and hyper-athletic cheetah (Acinonyx jubatus, M = 35-70 kg) compared to bigger and more robust felids such as lion (Panthera leo, M = 120-250 kg) [9].…”
Section: Discussionmentioning
confidence: 99%
“…In extinct sthenurine macropods, the thoracic limb displays features of a browsing adaptation with elongated manus, reduced lateral digits, slender radius, ulna and humerus, and a 'human-like' scapula, which may have enabled these animals to forage browse above their heads [8]. Hopping is likely not possible at body mass over ~160 kg, at which the distal tendons' safety factor (ratio of actual to ultimate stress) drops below 1, meaning that extinct 'giant kangaroos' would have used slower gaits [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There appear to be size limits on the use of hopping locomotion. Hopping mammals do not alter their locomotor posture with increasing body size; larger hoppers maintain the same crouched limb posture as smaller ones, which results in increasing tendon strain in the hind legs of larger kangaroos (McGowan et al 2008;Snelling et al 2017). The optimal size for hopping has been estimated at around 50 kg (which is around the average body weight of large extant kangaroos) (Bennett and Taylor 1995).…”
Section: Kangaroo Locomotion: Speed and Size Constraintsmentioning
confidence: 99%